Induced Mutation Of Fludioxonil Resistance In Penicillium Expansum Through Mutagens (Journal of Plant Disease Sciences, 2021)
Isolation of Penicillium expansum from infected apple fruits and their sensitivity was tested and found to be resistance and sensitive. These sensitive isolates of Penicillium expansum was used for further studies. Sensitive isolate (Pe-10) conidia of Penicillium expansum were treated with fludioxonil and various Physical and chemical treatment viz. spontaneous mutation (Sp), Ultraviolet rays (UV) and chemical mutagens such as Sodium Azide (SA), Ethyl Methane Sulphonate (EMS) and N-Nitro-N- Methyl Urea (NMU) due to the sensitive isolate of Penicillium expansum (Pe-10) was found that highly resistance, moderately resistance and few were resistance, highly resistance mutant were more pathogenic. It was seen that UV rays treatment gave higher percentage mutants followed by SP, NMU and EMS. Development of fungicide resistance in the resistant and sensitive isolates was studied by spontaneous mutation, UV, SA, EMS and MU gave higher percentage frequency and higher number of mutants than other treatments. Maximum mutants obtained through spontaneous, UV, EMS-treatment were also stated and highly pathogenic.
Keywords: Fludioxonil; Penicillium expansum; Mutagens